Metode valuasi ekonomi dalam pengambilan kebijakan lingkungan di sektor pertambangan - Yuniar, Farchani Putri (Journal of Economic, Business & Accounting Research, 2024)
The mining sector is a strategic pillar of national economic development. This sector provides a multiplier effect on people's lives but also has the potential for negative impacts on the environment. Economic valuation of natural resources and the environment is needed to determine the quantitative value of the goods and services produced. The purpose of writing this paper is to analyse the comparison of the use of economic valuation methods in environmental policymaking in the mining sector. Literature studies were carried out to look for references in the form of journals that were considered relevant to the purpose of the writing. Economic valuation methods such as cost-benefit analysis (CBA), real option valuation (ROV), and net present value (NPV) are crucial in the context of policymaking in the mining sector. These three methods can be used together or separately, depending on the context and characteristics of the project. The government and mining companies in Indonesia can utilise CBA for general policies, NPV for projects with a low level of uncertainty, and ROV for projects with a high level of uncertainty. The use of appropriate methods will provide a strong foundation for sustainable decision-making and support the development of an economically, environmentally, and socially responsible mining sector.